Pro-environmental behavior, green HRM practices, and green psychological climate: Examining the underlying mechanism in Pakistan - Li, Mingxing; ul Abidin, Rana Zain; Qammar, Rabia; Qadri, Syed Usman; Khan, Muhammad Kaleem; Ma, Zhiqiang; Qadri, Safwan; Ahmed, Haseeb; Khan, Hira Salah ud din; Mahmood, Shahid (Frontiers in Environmental Science, 2023)
The success of an organization's environmental sustainability objectives is contingent on the environmental behavior of its personnel. The present study was conducted to observe that how Green human resource management (GHRM) practice improves environmental performance (EP) through psychological green climate (PGC) and pro-environmental behavior (PEB). It’s also evaluating the moderating role of individual green value (IGV). Data were collected from HR professionals and Health officers directly engaged in human resource practices in private hospitals in Sialkot, Pakistan. To gather the responses, questionnaires were distributed, and PLS analysis was used to analyze the data. The findings showed that GHRM explains that the PGC stimulates employees to perform pro-environmental behaviors (PEB) for better environmental performance (EP). Furthermore, individual green value (IGV) moderates the employee's behavior for better environmental performance (EP). This research paper gives vital practical implications to top management and regulators in assuring employee engagement in applying Green human resource management (GHRM) practices. Keywords Green Human Resource Management (GHRM), Environmental Performance (EP), Green psychological climate (GPC), Green Behavior (GB), and Green Self-Efficacy (GSE)